Village Fund and its Impact on Poverty Alleviation in Kulon Progo Regency - Oktavia, Rina (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2020)
One of the objectives of the Village Fund is to alleviate poverty. Kulon Progo Regency is one of the regencies in at the provincial level and even national level. This study aims to 1) analyze the impact of the allocation of the village fund on village poverty in Kulon Progo Regency; 2) the strategic map of Village Fund management in Kulon Progo Regency; and 3) the Village Fund management with respect to poverty alleviation programs in Kulon Progo Regency. This study used several research methods to including the between the means, and descriptive quantitative and qualitative analysis. Results of the difference between the means  test  showed a significant difference in the poverty level in Kulon Progo Regency in the aftermath of the implementation of the Village Fund policy. Meanwhile, descriptive quantitative analysis results showed that 85 - 95 percent of Village Fund allocation for 2015-2017 period was on development programs, while qualitative analysis results identified differences in the management of Village Funds in Demangrejo and Kalirejo Villages. The difference in the management of the Village Fund in  Kalirejo and Demangrejo Villages lay in  the enthusiasm and contribution of the village community toward Village Fund management activities.